COMUNIDADES EN LÍNEA HISTORIA, COMUNICACIÓN Y TECNOLOGÍA EN LA EMERGENCIA DE COLECTIVOS MEDIÁTICOS - Siles González, Ignacio (Universidad de Costa Rica, 2005)
From oral communities to groups based on hypertextual exchanges, the article discusses first the history of user groups of communication mediums that have gathered around a technical object under the name of communities.  Second, a general landscape of online groups is presented, in order to understand their main characteristics as well as some of their most important contemporary debates.